KERJASAMA INDONESIA - AMERIKA SERIKAT MELALUI MUNICIPAL WASTE RECYCLING PROGRAM DALAM UPAYA MENCEGAH PENCEMARAN SAMPAH PLASTIK DI LAUT INDONESIA TAHUN 2016-2021 - Tiara Puspa Maharani, (2023)
This study aims to discuss the implementation of the Municipal Waste Recycling Program as part of the Indonesia-United States Cooperation in efforts to prevent plastic waste pollution in Indonesian seas in 2016-2021, from an environmental perspective, the concept of foreign aid, and the theory of program implementation. The method used is descriptive qualitative research to present a detailed description of the problems involved using primary and secondary data sources. The final results of this study indicate that efforts to reduce and handle marine plastic waste in Indonesia have received sufficient attention from various parties.. In cooperation with the United States through the Municipal Waste Recycling Program implemented in 2016-2021, this program has succeeded in contributing to two indicators of waste reduction and three indicators of Jakstranas waste management. In addition, all of the program's activities have been carried out in accordance with the pillars, strategies and objectives of the Indonesian National Action Plan for Combating Marine Plastic Waste. Even so, there are several goals and strategies that have not been fulfilled, including reducing waste in watersheds, canals, and prioritizing the processing of waste into energy. In this case, it is hoped that there will be wider efforts to reach these areas to support the reduction of leakage of land based marine debris in Indonesia.